Tinjauan Penggunaan Media Sosial dalam Etika Kristen - Deswita Sirait; Devi Hartati Pangaribuan; Diana Situmeang (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
Social media plays a crucial role in contemporary society, serving as a platform for individuals to connect, engage, and share information. The main issue addressed in this research is how social media can be utilized in the context of Christian ethics. The goal of this study is to investigate how social media is employed in the context of Christian ethics. This research approach involves the use of literature or literacy research. Christian ethics is the moral code followed by Christians, rooted in the teachings of God's word. The Bible serves as the cornerstone of God's teachings, providing guidance for Christian individuals living according to the principles of God's Kingdom. Every Christian should be mindful of their behavior on social media and always adhere to laws and regulations. Religious guidelines. In accordance with Christian ethics, social media usage should embody values like love, forgiveness, and respect towards others.